Towards New Perspectives on Toxoplasma gondii - El-Ashram, Saeed; Tellez-Isaias, Guillermo; Alali, Firas; Alouf, Abdulaziz (IntechOpen, 2023)
Towards New Perspectives on Toxoplasma gondii reflects the range of research activities and knowledge on this significant pathogenic protozoan parasite. The book addresses important developments in Toxoplasma, and covers a variety of topics, including the development of schizont stages of T. gondii in the primary cell culture of feline enterocytes, the effects of toxoplasmosis on host behavior, personality, and cognition, the three nutrient uptake portals in Toxoplasma tachyzoites, neuro-immunopathology, and the significant role that laboratories play in the diagnosis and prevention of Toxoplasma infection. This book will be an indispensable aid to many academics and scientists.